Exploring Intimate Partner Violence Survivors' Experiences of an Intervention Programme at the Mosaic Training, Service and Healing Centre - Gray, Wai'oca (Department of Psychology, 2023)
In the South African context, gender-based violence is related to a range of demographic characteristics such as ethnicity, gender, socio-economic status and sexuality, which contributes to varied forms of inequity. The lasting impact of Apartheid legislation, namely, the Group Areas Act, and the absence of fundamental resources in rural locations, has restricted the opportunities for black women from resource-poor rural areas to seek interventions for IPV. The aim of the study was to examine the way in which intimate partner violence (IPV) victim survivors talk about their experiences of an IPV intervention programme at the Mosaic, Training, Service and Healing Centre. This study is qualitative and uses an intersectional feminist theoretical framework and narrative research methodology. The sample of the study was women who have or are currently participating in the Earn to Survive IPV intervention programme at the Mosaic Training, Service and Healing Centre in Cape Town, South Africa. Unstructured face-to-face narrative interviews were conducted, and included questions which aimed to explore the way in which participants construct forms of identity for themselves through the process of sharing their experiences of the programme, participants' perceptions of the empowerment oriented focus of the programme and whether participants felt that the services provided by the programme were delivered in a way that promoted equity. Narrative analysis, in conjunction with thematic analysis methods were utilised to analyse the data. This study found that the participants benefitted socially, psychologically and tangibly-such as through the provision of grocery vouchers and transport fees- from their participation in Earn to Survive. This finding demonstrates the profoundly positive impact that IPV interventions have on IPV victim-survivors, and thus the importance of these interventions.